Granice kontroli Maszyneria władzy Jeremy Benthama - Nahirny, Rafał (Nowa Humanistyka, 2018)
Alongside Bentham the guardian of the weak and the subordinate, sensitive to other's suffering and deeply engaged in the fight for a better future and a more just legal system, there also exists a Bentham the unmitigated demiurge, with uncontrollable ambitions, incessantly creating soulless and authoritarian worlds of control and discipline. There is much that would suggest the English philosopher was pushed towards authoritarianism by the striving to provide a sense of security to the landed classes, and by fear of phenomena such as panic and social unrest. At the same time, as work on specific projects progressed, the noble impulses which often underpin them became weak, and they were replaced, under the influence of perfectionist fears and passions, by the thirst for complete control and total discipline. (excerpt from the book)